ANALISIS EFISIENSI PENGGUNAAN INPUT PRODUKSI USAHATANI JAGUNG MANIS DI DESA MAKU KECAMATAN DOLO KABUPATEN SIGI - Ronald Simorangkir; Max Nur Alam; Abdul Muis (Universitas Tadulako, 2014)
This study aimed to determine the effect of inputs on sweet corn production and to determine the efficiency of input use of sweet corn production in Maku Village Dolo Sub District Sigi Regency. The number of respondents was 31 farmers selected from 96 farmer population using a simple random sampling method. Cobb-Douglas production function and price efficiency analysis were performed to analyze data obtained. The analysis showed that simultaneously and partially land (X1), seeds (X2), fertilizer (X3), pesticides (X4) and labor (X5) were found to have very significant effect on the production of sweet corn. The use of land area (X1), fertilizer (X3) and pesticides (X4) had not yet been efficient, while that of seeds (X2) and labor (X5) were not efficient. Key Words : Cobb-Douglass function, efficiency, production input Influence.